Babad Demak : sejarah perkembangan Islam di tanah Jawa - Purwadi, 1971-; Maharsi, 1971- (Jogjakarta : Tunas Harapan, 2005)
History of Demak, the first Islamic sultanate in Java Island, and its role and position in historical development of Islam in Java.
Includes bibliographical references (p. 367-379).
Keywords: Islam -- Indonesia -- Java